Algorithms of modifying therapies in multiple sclerosis: dominant role of interferon beta - Cendrowski, Wojciech (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Background. Algorithms of the disease modifying therapies (DMT's) are mainstream of multiple sclerosis (MS) current treatment. Objective. To classify algorithms and to evaluate the efficacy of the DMT’s algorithms in MS. Method and patients. Analysis of algorithms aiming at improving the DMT's in 5 groups of MS patients was carried out: 1) in patients with worsening disability, 2) with very active disease, 3) showing a non-response to IFN beta, 4) in drug resistant malignant MS, 5) in patients with antibody neutralizing IFN beta (NAB+). Results. The first set of algorithms includes escalating DMT’s for progressive MS. Therapy began from administration of the Ist line drug and ended with combined treatment, plasmapheresis or natalizumab (NAT) alone. Algorithm of induction treatment showed efficacy of mitozantrone (MTX) + methylprednisolone (MP i.v.) with consecutive IFN beta in very active MS. These patients had lower relapse rate, decreased disability and the reduced number of new T2-related lesions than patients receiving IFN beta alone. Third series of the DMT's algorithms depended on change of treatments in non-responders to IFN beta. The improvement ensued after increase of IFN beta dose, sideeffects management, switching of IFN beta to other Ist and 2nd line drugs or NAT. Fourth kind of algorithm included immunoablation with consecutive rituximab or daclizumab in malignant MS. Small group of seropositive patients (NAB+) favourably responded to combined treatment with IFN beta and cyclic MP iv. Conclusions. The efficacy of MS treatment depends to some extent on choice of the proper DMT algorithm. Batter result of the DMT is more likely if algorithm is adapted to severity, clinical course of the disease and to the drug responsiveness.